2018
DOI: 10.1104/pp.18.00436
|View full text |Cite
|
Sign up to set email alerts
|

ZmbZIP4 Contributes to Stress Resistance in Maize by Regulating ABA Synthesis and Root Development

Abstract: In plants, bZIP (basic leucine zipper) transcription factors regulate diverse processes such as development and stress responses. However, few of these transcription factors have been functionally characterized in maize (Zea mays). In this study, we characterized the bZIP transcription factor gene ZmbZIP4 from maize. ZmbZIP4 was differentially expressed in various organs of maize and was induced by high salinity, drought, heat, cold, and abscisic acid treatment in seedlings. A transactivation assay in yeast de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(99 citation statements)
references
References 101 publications
(51 reference statements)
4
86
0
Order By: Relevance
“…Abscisic acid receptor PYL was one of the receptors, and CEY00_Acc03316 was annotated as abscisic acid receptor PYL, so it could be inferred that CEY00_Acc03316 may be a cold tolerance gene. The overexpression of bZIP transcription factor family proteins under stress was reported to improve the cold tolerance of plants (Chang et al, 2017;Ma et al, 2018). Therefore, CEY00_Acc13130 gene may be a cold tolerance gene.…”
Section: Screening and Analysis Of Cold Tolerance Related Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Abscisic acid receptor PYL was one of the receptors, and CEY00_Acc03316 was annotated as abscisic acid receptor PYL, so it could be inferred that CEY00_Acc03316 may be a cold tolerance gene. The overexpression of bZIP transcription factor family proteins under stress was reported to improve the cold tolerance of plants (Chang et al, 2017;Ma et al, 2018). Therefore, CEY00_Acc13130 gene may be a cold tolerance gene.…”
Section: Screening and Analysis Of Cold Tolerance Related Genesmentioning
confidence: 99%
“…Differential gene data were annotated to GO and KEGG were analyzed, and the cold tolerance related genes in kiwifruit were screened according to the previous studies on cold tolerance genes and related pathways (Hubbard et al, 2010;Kim et al, 2017;Li et al, 2018;Wang et al, 2017;Ma et al, 2018).…”
Section: Screening Of Differential Genesmentioning
confidence: 99%
“…Elsewhere, expression analysis of two maize bZIP TF genes ZmbZIP107 and ZmbZIP54 revealed that these two genes were highly elevated in a lead tolerant maize line when compared to a lead sensitive line in response to different treatments of lead (Zhang et al, 2017) (Table. 1). Recently, Ma et al (2018) demonstrated that ZmbZIP4 was induced by drought, cold, high salinity, ABA, and heat in maize seedlings. Overexpression of ZmbZIP4 led to an improved root system, increase in the number of lateral roots, and longer primary roots in transgenic maize.…”
Section: Bzip Tfs: Areb/abf Regulonmentioning
confidence: 99%
“…The essential roles of ABA and JA in plant stress responses and stress tolerance provide important clues for the development of stress-tolerant plants, and many successful studies reported stress-tolerant crops generated by modulation of ABA or JA responses. For example, activation or overexpression of OsPYL10, an ABA receptor increased ABA responses, leading to improved tolerance to drought [8], and overexpression of OsbZIP42 or heterologous expression of ZmbZIP4 (encoding positive regulators of ABA signaling) conferred drought tolerance in rice [9,10]. Additionally, a knock-out of the JA signaling repressor OsJAZ1 increased JA sensitivity and drought tolerance; conversely, overexpression of OsJAZ1 reduced JA sensitivity and drought tolerance [11].…”
Section: Introductionmentioning
confidence: 99%